Role of skeletal muscle satellite cells in the repair of osteoporotic fractures mediated by β‐catenin. Issue 2 (17th February 2022) - Jin, Zhenxiong; Da, Weiwei; Zhao, Yongjian; Wang, Tengteng; Xu, Hao; Shu, Bing; Gao, Xiang; Shi, Qi; Ma, Yong; Zhang, Yan; Wang, Yongjun; Tang, Dezhi
Abstract: Background: Osteoporosis is a metabolic disease, and osteoporotic fracture (OPF) is one of its most serious complications. It is often ignored that the influence of the muscles surrounding the fracture on the healing of OPF. We aimed to clarify the role of skeletal muscle satellite cells (SMSCs) in promoting OPF healing by β‐catenin, to improve our understanding of SMSCs, and let us explore its potential as a therapeutic target. Methods: Skeletal muscles were obtained from control non‐OPF or OPF patients for primary SMSCs culture ( n  = 3, 33% females, mean age 60 ± 15.52). Expression of SMSCs was measured. In vivo, 3‐month‐old female C57BL/6 mice underwent OVX surgery. Three months later, the left tibia fracture model was again performed. The control and the treatment group ( n  = 24, per group, female). The treatment group was treated with an agonist (osthole). Detection of SMSCs in muscles and fracture healing at 7, 14, and 28 three time points ( n  = 8, 8, 8, female). To further clarify the scientific hypothesis, we innovatively used Pax7‐Cre ERT2/+ ;β‐catenin fx/fx transgenic mice ( n  = 12, per group, male). Knock out β‐catenin in SMSC to observe the proliferation and osteogenic differentiation of SMSCs, and OPF healing. In vitro primary cells of SMSCs from 3‐month‐old litter‐negative β‐catenin fx/fx transgenic mice. After adenovirus‐CRE transfection, the myogenic and osteogenic differentiation of SMSC was observed. Results: We find that human SMSCs reduced proliferation and osteogenic differentiation in patients with OPF (−38.63%, P  < 0.05). And through animal experiments, it was found that activation of β‐catenin promoted the proliferation and osteogenic differentiation of SMSC at the fracture site, thereby accelerating the healing of the fracture site (189.47%, P  < 0.05). To prove this point of view, in the in vivo Pax7‐Cre ERT2/+ ;β‐catenin fx/fx transgenic mouse experiment, we innovatively found that knocking out β‐catenin in SMSC will cause a decrease in bone mass and bone microstructure, and accompanied by delayed fracture healing (−35.04%, P  < 0.001). At the same time, through in vitro SMSC culture experiments, it was found that their myogenic (−66.89%, P  < 0.01) and osteogenic differentiation (−16.5%, P  < 0.05) ability decreased. Conclusions: These results provide the first practical evidence for a direct contribution of SMSCs to promote the healing of OPF with important clinical implications as it may help in the treatment of delayed healing and non‐union of OPFs, and mobilization of autologous stem cell therapy in orthopaedic applications.